МЕТОДЫ ОБУЧЕНИЯ ПИСЬМУ В НАЧАЛЬНЫХ КЛАССАХ - Аширбекова, А.Б. (SCIENCE and SOCIETY, 2022)
This article provides information on how to improve the writing skills of elementary school students and develop them in an effective way. In addition, it helps language teachers to choose classes according to their knowledge and age. Many teachers have trouble learning to write as writing is considered to be one of the hardest skills of all. That is why it is so important to teach this skill. Language learners also have writing difficulties. Because they do not know where to start and how to write this assignment.
Keywords: writing process; writing; proofreading; components; writing skills; effective writing; draft; mental mapping